PENGEMBANGAN MAGIC CROSSWORD PUZZLE SEBAGAI MEDIA PEMBELAJARAN IPA UNTUK SISWA KELAS V SEKOLAH DASAR - Ifa Seftia Rakhma; Unik Widyaningsih; Lilik Mawartiningsih (Universitas Muria Kudus, 2016)
The purpose of this research is to develop magic crossword puzzle media in the material ofnatural phenomena. This research is a Research and Development. Implementation magiccrossword puzzle media using one group pretest-posttest control design with the subjects are fifthgrade students SDN 2 Gedong Mulyo Mulyo academic year 2016/ 2017. The results magiccrossword puzzle media consists of two parts, front page and back page. The front page iscrossword puzzle and the back page is pieces of pape. The results validate from two validatorsare media developed by the researchers included in the category of valid use in the fiftth grade ofelementary school. Magic crossword puzzle effective in material natural phenomena from thepretest result is 55,56 % posttest result is 94,4 %. Students activity is 32 % and teacher activity is38 %. Students also give good respon to magic crossword puzzle meda.